An Expectancy Theory Approach to Group Coordination: Expertise, Task Features, and Member Behavior. (1st April 2016) - Baumann, Michael R.; Bonner, Bryan L.
Abstract: Working in a group requires coordination. The current paper examines coordination in terms of member‐level behavioral choices. Extending expectancy theory to a collaborative group setting, we interpret past findings on expertise and hypothesize that component features (specifically their difficulty and worth relative to each other) impact member behavior and hence coordination both directly and by moderating the role of expertise. Findings were largely as predicted, suggesting that an expectancy theory perspective may be a useful tool for the study and understanding of coordination. An exploratory examination of recordings of group interaction suggested that although most of our groups discussed coordination strategies, the strategies discussed did not generally map to the behavioral choices observed. Implications for coordination in general and transactive memory specifically are discussed. Copyright © 2016 John Wiley & Sons, Ltd.